A systematic review and meta-analysis of the diagnostic accuracy of pyruvate kinase M2 isoenzymatic assay in diagnosing colorectal cancer - Uppara, Mallikarjuna (World J Surg Oncol, 2015)
BACKGROUND: Screening programmes exist in many countries for colorectal cancer. In recent years, there has been a drive for a non-invasive screening marker of higher sensitivity and specificity. Stool-based pyruvate kinase isoenzyme M2 (M2-PK) is one such biomarker under investigation. The aim of this systematic review and meta-analysis is to determine the diagnostic accuracy, sensitivity and specificity of M2-PK as a screening tool in colorectal cancer. METHODS: A literature search of Ovid Medline, EMBASE and Google Scholar was carried out. The search strategy was restricted to human subjects and studies published in English. Data on sensitivity and specificity were extracted and pooled. Statistical analysis was conducted using summary receiver operating characteristic (SROC) curve methodology. RESULTS: A total of eight studies were suitable for data synthesis and analysis. Our analysis showed a pooled sensitivity and specificity for M2-PK to be 79% (CI 73%–83%) and 80% (CI 73%–86%), respectively. The accuracy of M2-PK was 0.85(0.82–0.88). CONCLUSION: Faecal M2-PK assay has a relatively good sensitivity and specificity and high accuracy for screening colorectal cancer.